Management Of Sponsorship Activities In The Pre-Implementation Stage Of Ephics 2.0 2023 By The Prima International Tourism Polytechnic - Ningsih, Widia; Wibowo, Riyanto (Jurnal Toursci, 2025)
Background. Along with the development of the era of globalization, which requires every individual to have a higher education to provide for the future. EPHICS 2.0 is here as a platform for the younger generation to showcase their capabilities and foster cooperative relationships between educational institutions in the tourism sector. Purpose. Knowing the management of sponsorship activities at the pre-implementation stage of EPHICS 2.0 2023, and understanding the obstacles and solutions to be carried out. Method. The type of research employed is qualitative, with a data analysis method that utilizes descriptive analysis. Result. The Prima International Tourism Polytechnic is holding the EPHICS 2.0 2023 Annual Event. Conclusion. The management of sponsorship activities during the sponsorship search process is conducted through a comprehensive procedure. The management was carried out by the Sponsorship team from start to finish. However, not all stages are carried out sequentially by the Sponsorship team. Such as the process of returning sponsorship contract forms and NPWP for some companies is carried out at the stage after the event. Implementation. The sponsoring company must be further improved so that the preparation process runs well.